2019
DOI: 10.1016/j.bpj.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Oscillations of Epithelial Cell Sheets

Abstract: Morphological changes during development, tissue repair, and disease largely rely on coordinated cell movements and are controlled by the tissue environment. Epithelial cell sheets are often subjected to large-scale deformation during tissue formation. The active mechanical environment in which epithelial cells operate have the ability to promote collective oscillations, but how these cellular movements are generated and relate to collective migration remains unclear. Here, combining in vitro experiments and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 77 publications
4
133
3
Order By: Relevance
“…We showed that the cell could undergo cycles of expansion and contraction in the case of a Rac-like GTPase that pushes out the cell edges. Recent work on cell oscillations (in the context or confined epithelial sheets) is given in (Peyret et al 2019), and a review of cycles of protrusion and retraction in experimental and theoretical models of the cell edge is found in (Ryan et al 2012). Cycles also occur in paper by (Dierkes et al 2014), who consider a similar treatment of dilution (of myosin concentration) when the cell stretches, and a mechanical contractile unit driven by myosin.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the cell could undergo cycles of expansion and contraction in the case of a Rac-like GTPase that pushes out the cell edges. Recent work on cell oscillations (in the context or confined epithelial sheets) is given in (Peyret et al 2019), and a review of cycles of protrusion and retraction in experimental and theoretical models of the cell edge is found in (Ryan et al 2012). Cycles also occur in paper by (Dierkes et al 2014), who consider a similar treatment of dilution (of myosin concentration) when the cell stretches, and a mechanical contractile unit driven by myosin.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of collective behaviors, much effort has gone towards reductionist assays that restrict degrees of freedom and ensemble size to simplify analysis and interpretation. One powerful approach is to confine a tissue within predefined boundaries using micropatterning to create adhesive and non-adhesive regions (6)(7)(8)(9)(10)(11). Such confinement mimics certain in vivo contexts such as constrained tumors as well as aspects of compartmentalization during morphogenesis (12).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining timescale ⌧ r , for the magnitude of substrate friction/mechanical relaxation, determines how far local deformations propagate over one period of oscillation, which explains the finite length scale of the instability. In contrast to previous approaches relying on polar migration forces [5][6][7][8], this minimal model requires only scalar active terms to produce patterns of density, velocity and ERK at finite length and time scales. We also note that density waves are abolished by inhibition [5], but also overactivation of ERK ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, how mechanical and chemical signaling are integrated at the cellular level to give rise to such collective behaviors remains unclear. We address this by focusing on the highly conserved phenomenon of spatio-temporal waves of density [2,[4][5][6][7][8] and ERK/MAPK activation [9][10][11], which appear both in vitro and in vivo during collective cell migration and wound healing. First, we propose a biophysical theory, backed by mechanical and optogenetic perturbation experiments, showing that patterns can be quantitatively explained by a mechano-chemical coupling between three-dimensional active cellular tensions and the mechano-sensitive ERK/MAPK pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation